Value Chain Analysis as a Foundation for Business Development Strategy - Ersal, Agung Pratama; Pradana, Bayu Ilham (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose –  This study aims to analyze the primary and support activities implemented by Pesans.id, a food and beverage startup in Bogor, West Java, and to formulate business development strategies based on Value Chain Analysis. Design/Methodology/Approach – This study employs a descriptive qualitative research approach. The research focuses on the value chain activities of Pesans.id, with data collected from internal members of the company and consumers who have purchased Pesans.id products at least once. Data were gathered through observations, interviews, and documentation, then analyzed using Value Chain Analysis through data collection, data reduction, data presentation, and conclusion drawing. Findings – The results indicate that Pesans.id’s value chain implementation aligns with the Value Chain Analysis framework, where primary activities serve as the main drivers of business operations and support activities strengthen the effectiveness of those activities. Pesans.id demonstrates competitive advantages through product uniqueness, superior quality control of raw materials, improved standard operating procedures (SOPs), and enhanced customer service. These strengths support the implementation of a differentiation strategy as the foundation for future business development by increasing customer value, purchase intention, and repurchase behavior. Originality/Value This research is original in applying value chain analysis to a local food and beverage startup context. The findings provide practical value by offering strategic recommendations to strengthen differentiation strategies and support long-term business development.